The integration of Microsoft Word tools to facilitate writing among TESL teacher trainees - Puteh, Fatimah (2010)
This study investigated the integration of Microsoft Word tools among TESL teacher trainees to facilitate their writing. The focus of this study is on the use of Microsoft Word tools, the dependency on Microsoft Word tools and the problems faced while using Microsoft Word tools by the TESL teacher trainees. For this study, a total of 50 TESL teacher trainees who consist of third year and fourth year TESL students of Universiti Teknologi Malaysia were chosen as the sample. Questionnaire has been used as a means of data collection in order to identify the integration of Microsoft Word tools in the writing of TESL teacher trainees. The data collected have been analysed with the aid of Microsoft Excel. The findings of the study indicate that the TESL teacher trainees utilised most of the tools available in Microsoft Word. They are highly dependent on the tools as these tools facilitate their writing process and they only face problems while using the Synonym feature within Microsoft Word. Some suggestions have also been made in order to further improvise the study by altering the scope and by focusing on only a version of Microsoft Word when collecting data.